2017
DOI: 10.1136/archdischild-2017-313060
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic delay in Canadian children with inflammatory bowel disease is more common in Crohn’s disease and associated with decreased height

Abstract: Diagnostic delay was more common in CD and associated with height impairment that persisted 1 year after presentation. The greatest contributor to time to diagnosis was time from symptom onset to referral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
55
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 21 publications
4
55
3
1
Order By: Relevance
“…This study was unable to comment on the prevalence of anti-TNF medication over time due to incomplete data. Data from 1998 to 2013 from Larsen et al concluded that there was decreased surgery in children with UC and a trend towards decreased surgery in CD patients over time, with a parallel increase in anti-TNF use in both groups 36. Both studies include data predating routine use of early anti-TNF therapy, and the authors conclude that analysis of more recent data may reveal a true decrease or delay in surgery during childhood alongside an increase in early anti-TNF use, as seen in our work.The assessment of growth outcomes in Crohn's disease can be used as a proxy measure of effective treatment, with improved growth reflecting adequately treated patients.…”
mentioning
confidence: 99%
“…This study was unable to comment on the prevalence of anti-TNF medication over time due to incomplete data. Data from 1998 to 2013 from Larsen et al concluded that there was decreased surgery in children with UC and a trend towards decreased surgery in CD patients over time, with a parallel increase in anti-TNF use in both groups 36. Both studies include data predating routine use of early anti-TNF therapy, and the authors conclude that analysis of more recent data may reveal a true decrease or delay in surgery during childhood alongside an increase in early anti-TNF use, as seen in our work.The assessment of growth outcomes in Crohn's disease can be used as a proxy measure of effective treatment, with improved growth reflecting adequately treated patients.…”
mentioning
confidence: 99%
“…Riccuito et al analysed features associated with a delay in diagnosis. In univariate analysis diarrhoea (OR 0.29), blood per rectum (OR 0.33), bloody diarrhoea (OR 0.25) and weight loss (OR 0.38) were all significantly associated with decreased risk of a diagnostic delay, reflecting the most common symptoms seen in practice 1. The authors did not find any association between age, gender, socioeconomic background or, interestingly, a family history of IBD.…”
mentioning
confidence: 80%
“…The findings indicate that the greatest time was from onset of symptoms to referral to specialist services (89 days, IQR 48–250), with the interval between referral to specialist services and diagnosis making up a minority of the time (15 days, IQR 7–45) 1. Perhaps the most concerning finding was that 20% of patients were waiting over a year from symptoms to diagnosis 1. The results need cautious interpretation.…”
mentioning
confidence: 92%
See 2 more Smart Citations